Database systems design, implementation, and management - Coronel, Carlos; Morris, Steven (Cengage Learning, 2017)
Give students a solid foundation in database design and implementation with the practical and easy-to-understand approach in DATABASE SYSTEMS: DESIGN, IMPLEMENTATION, AND MANAGEMENT, 12E. Filled with diagrams, illustrations, and tables, this market-leading text provides in-depth coverage of database design. Students learn the key to successful database implementation is the proper design of databases to fit within a larger strategic view of the data environment. This book combines a clear, straightforward writing style with an outstanding balance of theory and practice. Students gain the hands-on skills to make them attractive to employers. Updates include the latest coverage of cloud data services and a new chapter on Big Data Analytics and NoSQL, including related Hadoop technologies. In addition, new review questions, problem sets, and cases offer multiple opportunities for students to test their understanding and develop useful design skills.